The Influence of Anti-Hiv-1 Specific IgY In Inhibiting HIV-1 Infection in Binding Phase with Syncytium Examination of CD4 Receptor Density Using the Flowcytometry Method - Maskoep, Wiwiek Indriyani; Nasronudin, Nasronudin; Khairunisa, Siti; Sudjarwo, Sri Agus (Folia Medica Indonesiana, 2020)
HIV/ AIDS infections have increased and spread very quickly in the world, including in Indonesia. The absence of an effective vaccine and the fact that antiretroviral drugs can only suppress the progression of infection but cannot eradicate it lead to the efforts to find materials containing immunoglobulins that can replace the immune system which greatly declines in HIV/ AIDS patients. The successful use of specific IgY in other studies opens up opportunities for the use of anti-HIV-1 specific IgY as passive immunotherapy. This type of research is true experimental research design with post-test only control group design. IgY was obtained from Lohmann Laying hens chicken eggs immunized with the inactivated HIV-1 virus. The concentration of IgY was determined using the Bradford method and then the characterization test was continued using the AGPT, ELISA, SDS-PAGE and Western blot tests which showed anti-HIV-1 specific IgY. The results of the test showed specific anti-HIV-1 IgY was effective in inhibiting the formation of syncytium in HIV-1 infection against CD4+ T lymphocytes in the binding phase (entry stage) in the treatment group p-value 0.000 (p <0.05). The results of CD4 receptor density tests using the Flowcytometry method showed that specific anti-HIV-1 IgY was effective in inhibiting HIV-1 infection against CD4+ T lymphocytes in the binding phase (entry stage) in the treatment group p-value 0.047 (p <0.05).HIV/ AIDS infections have increased and spread very quickly in the world, including in Indonesia. The absence of an effective vaccine and the fact that antiretroviral drugs can only suppress the progression of infection but cannot eradicate it lead to the efforts to find materials containing immunoglobulins that can replace the immune system which greatly declines in HIV/ AIDS patients. The successful use of specific IgY in other studies opens up opportunities for the use of anti-HIV-1 specific IgY as passive immunotherapy. This type of research is true experimental research design with post-test only control group design. IgY was obtained from Lohmann Laying hens chicken eggs immunized with the inactivated HIV-1 virus. The concentration of IgY was determined using the Bradford method and then the characterization test was continued using the AGPT, ELISA, SDS-PAGE and Western blot tests which showed anti-HIV-1 specific IgY. The results of the test showed specific anti-HIV-1 IgY was effective in inhibiting the formation of syncytium in HIV-1 infection against CD4+ T lymphocytes in the binding phase (entry stage) in the treatment group p-value 0.000 (p <0.05). The results of CD4 receptor density tests using the Flowcytometry method showed that specific anti-HIV-1 IgY was effective in inhibiting HIV-1 infection against CD4+ T lymphocytes in the binding phase (entry stage) in the treatment group p-value 0.047 (p <0.05).